Use of Cidofovir for Safe Transplantation in a Toddler with Acute Liver Failure and Adenovirus Viremia. (9th November 2022) - Christian, Vikram J.; Sarwar, Raiya; Resch, Joseph C.; Lim, Sarah; Somani, Arif; Larson-Nath, Catherine; McAllister, Shane; Thielen, Beth K.; Adeyi, Oyedele; Chinnakotla, Srinath; Bhatt, Heli
Abstract : Background . Since October 2021, there have been more than 500 cases of severe hepatitis of unknown origin in children reported worldwide, including 180 cases in the U.S. The most frequently detected potential pathogen to date has been adenovirus, typically serotype 41. Adenovirus is known to cause a self-limited infection in the immunocompetent host. However, in immunosuppressed individuals, severe or disseminated infections may occur. Method . We present the case of a two-year-old female who presented with cholestatic hepatitis and acute liver failure (ALF). Work up for etiologies of ALF was significant for adenovirus viremia, but liver biopsy was consistently negative for the virus. The risk for severe adenoviral infection in the setting of anticipated immunosuppression prompted us to initiate cidofovir to decrease viral load prior to undergoing liver transplantation. Result . Our patient received a successful liver transplant, cleared the viremia after 5 doses of cidofovir, and continues to maintain allograft function without signs of infection at the time of this report, 5 months posttransplant. Conclusion . Recent reports of pediatric hepatitis cases may be associated with adenoviral infection although the exact relationship is unclear. There is the possibility of the ongoing SARS-CoV-2 environment, or other immunologic modifying factors. All patients presenting with hepatitis or acute liver failure should be screened for adenovirus and reported to state health departments. Cidofovir may be used to decrease viral load prior to liver transplantation, to decrease risk of severe adenoviral infection.